Pelaksanaan Model Pembelajaran Inquiry Learning dalam Kurikulum Merdeka pada Mata Pelajaran PAI di SDN 12 Koto Tangah - Fajri, Hasan; Charles, Charles (TSAQOFAH, 2023)
Elementary Schools have an important role in shaping the character of students, with basic educational concepts with the aim of forming student character from an early age. Based on the observations made by the author at SDN 12 Koto Tangah, it is known that there is still a lack of understanding of teachers in the application of the inquiry learning learning model. The type of research used in this research is descriptive qualitative in the form of field research. The data sources with key informants are educators and student supporting informants. data collection techniques by observation, documentation and interviews. The results showed that the implementation of the inquiry learning model in PAI subjects at SDN 12 Koto Tangah included implementation steps: orientation, formulating problems, submitting hypotheses, collecting data, testing hypotheses, formulating problems. However, in this effort there are inhibiting and supporting factors in forming the honest character of students. includes from the school environment, from within students, environmental factors around. includes from the school environment, from within students, environmental factors.